Clays and Clay Minerals, Vol. 55, No. 6, 565–571, 2007. - Cho, Yunchul; Komarneni, Sridhar (The Clay Minerals Society, 2007)
The weathering stages of K-depleted biotite, K-depleted phlogopite, and natural biotite were investigated using hydrothermalt reatment with AlCl3 solution at 200ºC for 12 to 72 h. Although there were some differences in the degree of weathering of the two K-depleted micas, both first transformed to hydroxy-Al interlayered vermiculite (HIV), which then altered to kaolinite. In case of the natural biotite, the biotite first transformed to a K-depleted mica-like phase, which then altered to kaolinite. The natural biotite had resisted weathering to kaolinite more than did the K-depleted biotite, as expected. The K-depleted phlogopite had less resistance in weathering to kaolinite than the K-depleted biotite. The transformation process changed the color of the micas. The K-depleted biotite changed from greenish-black through yellow to pale gray whereas the natural biotite changed from greenish-black through beige to yellow. However, in the case of K-depleted phlogopite, there was no significant color change during the transformation process. The presence of the interlayer K+ ions and the structuralFe 2+ ions in mica appear to have contributed to the differences in the degree of weathering to kaolinite among the micas investigated.
Synthesis Of Kaolinite From Micas And K-depleted Micas
Clays and Clay Minerals, Vol. 55, No. 6, 565–571, 2007. Synthesis Of Kaolinite From Micas And K-depleted Micas. Yunchul Cho; Sridhar Komarneni. DOI: 10.1346/CCMN.2007.0550603. Copyright © 2007, The Clay Minerals Society
Keywords: Periodicals; Geology; Hydrothermal Treatment; Hydroxy Al-interlayered Vermiculite (HIV); Kaolinite; K-depleted Biotite; K-depleted Phlogopite; Transformation; Weathering